The Role of Land Associates Officials (PPAT) in Collection of BPHTB Tax on Land & Building Transactions for Sale & Building - Tafana Bella Marinda; Akhmad Khisni; Ngadino Ngadino (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2020)
The legal act of transferring rights to land and/or buildings must always be followed by the making of the necessary deeds, as specifically regulated on this matter. Which deeds must be made by the competent official for this, namely the Official for Making Land Deeds (PPAT), where in certain cases the deed is made by a notary. Thus, the government in its issued regulation has assigned the official making the deed to participate in supervising the payment of taxes payable on the said land and/or building transactions. However, in its implementation there are still many obstacles that arise, especially there is still tax avoidance in land transactions, and a lack of understanding of the calculation and payment of Land Rights Acquisition Tax (BPHTB) by taxpayers, which results in the main tax function to fill State cash receipts, which are often referred to as budgetary functions, which are not well implemented. In the collection of Land Rights Acquisition Fees (BPHTB) in connection with the deed he makes, it is hoped that the Notary as PPAT will play an active role requiring payment of Land Rights Acquisition Fee (BPHTB) in transferring rights to land and buildings, which after the agreement is made and the payment transaction is made, the tax must be paid as soon as possible, then its correctness is checked so that the deed can be signed immediately.